Metaphorical COVID-19 Concepts: A Corpus Pragmatics Study - Shameem Alsalami (آداب الكوفة, 2023)
This paper investigates the way pragmatics and corpus linguistics can benefit from each other through tackling metaphorical language. The metaphors of COVID-19 and how they can be analyzed both qualitatively and quantitively in the realm of corpus pragmatics analysis will be focused on. Significantly, the basic aim of the paper is to shed light on the very nature and use of metaphorical concepts, particularly their pragmatic functions. Moreover, the paper seeks to uncover the fundamental similarities between pragmatics as a linguistic discipline and metaphor as a linguistic tool, since both represent the essence of a hidden or implied meaning. Pragmatic theory views metaphor as a speech act. In other words, a speaker is using signs with a literal meaning to create a new intentional structure which has no literal meaning. To answer the research questions set by the paper, the study adopts a corpus pragmatic analysis in order to trace the recent spread of metaphorical language concerning COVID-19. The combination of pragmatics and corpus linguistics in this study led to the use of methodologies from both fields. Regarding metaphorical concepts, the corpus analysis proves that there is no one-to-one relation between form and function. The speech acts as well as the politeness strategies are in constant change in accordance with their context. Yet, the metaphors expressed are most frequently based on the choice of words and their accompanying referential meaning. Most notably, the ‘War Metaphors’ and the ‘Fire Metaphors’ have been particularly appropriate and versatile in reference to the pandemic and the process of combatting it. Therefore, this research also attempts to discuss the different types of metaphors used referring to the pandemic from a corpus pragmatics perspective